Retrospective Longitudinal Analysis: Loss to Follow Up Undergoing Antiretroviral Therapy in Kerti Praja Foundation Bali 2002-2012 - Desak Nyoman Widyanthini; Anak Agung Sawitri Sawitri; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Lower loss to follow up (LTFU) is one indicator of the success of antiretroviral therapy (ART). In 2013 the Indonesian Ministry of Health reported that the cumulative percentage of LTFU was as high as 17.3%. To date, there has been no retrospective research into LTFU on people living with HIV/AIDS (PLHIV) in Bali, particularly to investigate PLHIV client characteristics. Methods: This descriptive longitudinal study was conducted to analyze secondary data from records of PLHIV initiating ART between 2002-2012 at Clinic Amertha, Kerti Praja Foundation (YKP). The sample was PLHIV receiving ART at the YKP from 2002-2012 that had first received ART in YKP and had minimum 2 consultations. Data used was that recorded in the medical records. Variables were: age, gender, occupation, the presence of ART supervisor, and HIV transmission mode. Data were analyzed descriptively to obtain insight into characteristics of LTFU clients per 100 person years (PY). Length of time since LTFU was assessed. Results: The sample was 548: 77 (14,1%) were LTFU with crude incidence of LTFU at 5.15 per 100 PY. Median time of LTFU was not reached in this study, because of the low outcome incidence. Specific LTFU incidence was higher in women (6.6 per 100 PY), younger age (6.0 per 100 PY), and female sex workers (7.3 per 100 PY). Lack of ART supervisor (9.3 per 100 PY) and homosexual (9.1 per 100 PY) also had higher LTFU incidence. Conclusion: Specific LTFU incidence was higher in women, younger age, female sex workers, lack of ART supervisor, and homosexual.